2019
DOI: 10.1186/s40169-019-0244-7
|View full text |Cite
|
Sign up to set email alerts
|

From fiction to science: clinical potentials and regulatory considerations of gene editing

Abstract: Gene editing technologies such as CRISPR/Cas9 have emerged as an attractive tool not only for scientific research but also for the development of medicinal products. Their ability to induce precise double strand breaks into DNA enables targeted modifications of the genome including selective knockout of genes, correction of mutations or precise insertion of new genetic material into specific loci. Gene editing‐based therapies hold a great potential for the treatment of numerous diseases and the first products … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 116 publications
(118 reference statements)
0
17
0
Order By: Relevance
“…Efforts have also been made to improve HDR by fusing Cas9 to RecA (RAD51 in eukaryotes), which plays a key role in homologous recombination (Cai et al, 2019;Kurihara et al, 2020), or by altering the conformational checkpoints for Cas9 binding to DNA (Kato-Inui et al, 2018). No product for therapeutic gene editing has yet been approved, but the first clinical trials based on this technology have demonstrated the safety of this approach (Schacker and Seimetz, 2019). However, as gene editing permanently modifies the DNA, several biosafety concerns have been raised concerning the induction of off-target DSBs and increases in genomic instability (Mills et al, 2003).…”
Section: Gene Editingmentioning
confidence: 99%
See 1 more Smart Citation
“…Efforts have also been made to improve HDR by fusing Cas9 to RecA (RAD51 in eukaryotes), which plays a key role in homologous recombination (Cai et al, 2019;Kurihara et al, 2020), or by altering the conformational checkpoints for Cas9 binding to DNA (Kato-Inui et al, 2018). No product for therapeutic gene editing has yet been approved, but the first clinical trials based on this technology have demonstrated the safety of this approach (Schacker and Seimetz, 2019). However, as gene editing permanently modifies the DNA, several biosafety concerns have been raised concerning the induction of off-target DSBs and increases in genomic instability (Mills et al, 2003).…”
Section: Gene Editingmentioning
confidence: 99%
“…Over the last decade, more sophisticated and precise editing tools have rendered genome engineering not only promising for genebased therapeutic approaches, but also useful as a technique for basic biology, genetic diagnosis and drug discovery purposes (Doudna, 2020;Li et al, 2020;Sandoval et al, 2020;Wertz et al, 2020). Indeed, therapeutic genome editing is no longer a concept for the distant future, and several ex vivo and in vivo therapeutic approaches are currently undergoing clinical testing for the treatment of various diseases (Schacker and Seimetz, 2019;Li et al, 2020). In this review, we describe the various genome editing tools available and summarize some of the preclinical studies of in vivo CNS genome editing published to date, while discussing current limitations and alternative approaches to overcome some of the bottlenecks.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the previously described gene therapy approaches based on both gene supplementation and gene suppression strategies, recent advances on genome editing tools by CRISPR/Cas technology allow the correction of a specific mutation at a genomic level [18]. Due to the huge treatment possibilities of such revolutionary genome editing tools, the number of scientific publications in this area has considerably increased since 2014, and many clinical trials are underway, especially in cancer and pathological disorders of the blood and eye [19]. In any case, although highly Pharmaceutics 2020, 12, 198 4 of 29 promising, still some concerns mainly related to the delivery strategy, the possibility of permanent off target effects, or the efficiency to repair the mutation in a controlled manner need to be resolved before reaching the market [20].…”
Section: Introductionmentioning
confidence: 99%
“… 12 Another method has explored utilizing gene editing systems to mutate host factors that in order to create HIV-1-resistant CD4 + T cells or permanently inactivated the proviral DNA, thereby reducing the reservoir. 13 , 14 …”
Section: Introductionmentioning
confidence: 99%